Sex offenders with intellectual disability referred to levels of community and secure provision: Comparison and prediction of pathway. (3rd December 2012) - Carson, Derek; Lindsay, William R.; Holland, Anthony J.; Taylor, John L.; O'Brien, Gregory; Wheeler, Jessica R.; Steptoe, Lesley; Johnston, Susan
<x xml:space="preserve">Abstract</x> Purpose To compare characteristics of sex offenders with an intellectual disability (ID) referred to community‐based and different levels of secure services. To identify those characteristics, which predict referrals to community‐based or secure services. Methods A total of 131 cases of sex offenders with ID referred to an ID service in a number of health board regions in the UK in 2002 (and 2003 for high secure referrals) were reviewed. Data were collected on demographic information, ethnicity, level of learning disability, possible medical diagnoses, psychiatric diagnoses, abuse experienced in childhood, living circumstances, employment or occupation, referring agent, legal status on day of referral, index behaviour, age at time of index behaviour, charges, legal status on day of index behaviour, previous problematic behaviour, and previous offending. Data were entered into a binomial logistic regression model in an attempt to predict the referrals to community‐based services. Results Numerous characteristics were found to be associated with the different levels of service security, but only two predictor variables retained a strong association with community or secure referrals in the model. The likelihood of the offender being referred to a community‐based service increased if they were based in the community at the time of the index behaviour and decreased as the diversity of problematic behaviour exhibited by the offenders increased. Conclusions Given the relatively high proportion of referrals to community‐based services and the fact that many of these referrals had a complicated offence history, it is important that community‐based services are properly equipped and resourced to deal with such referrals. In particular, the case is made that services for sexual offenders with ID at all levels of security should at least have available interventions directed at aggression.